Arabidopsis Glutaredoxin S17 Contributes to Vegetative Growth, Mineral Accumulation, and Redox Balance during Iron Deficiency - Yu, Han; Yang, Jian; Shi, Yafei; Donelson, Jimmonique; Thompson, Sean M.; Sprague, Stuart; Roshan, Tony; Wang, Da-Li; Liu, Jianzhong; Park, Sunghun; Nakata, Paul A.; Connolly, Erin L.; et al. (Frontiers in Plant Science, 2017)
Iron (Fe) is an essential mineral nutrient and a metal cofactor required for many proteins and enzymes involved in the processes of DNA synthesis, respiration, and photosynthesis. Iron limitation can have detrimental effects on plant growth and development. Such effects are mediated, at least in part, through the generation of reactive oxygen species (ROS). Thus, plants have evolved a complex regulatory network to respond to conditions of iron limitations. However, the mechanisms that couple iron deficiency and oxidative stress responses are not fully understood. Here, we report the discovery that an Arabidopsis thaliana monothiol glutaredoxin S17 (AtGRXS17) plays a critical role in the plants ability to respond to iron deficiency stress and maintain redox homeostasis. In a yeast expression assay, AtGRXS17 was able to suppress the iron accumulation in yeast ScGrx3/ScGrx4 mutant cells. Genetic analysis indicated that plants with reduced AtGRXS17 expression were hypersensitive to iron deficiency and showed increased iron concentrations in mature seeds. Disruption of AtGRXS17 caused plant sensitivity to exogenous oxidants and increased ROS production under iron deficiency. Addition of reduced glutathione rescued the growth and alleviates the sensitivity of atgrxs17 mutants to iron deficiency. These findings suggest AtGRXS17 helps integrate redox homeostasis and iron deficiency responses.